Working Welsh : a guide to the mechanics of the language - King, Gareth, 1955- (New York : Routledge, 2020)
"Working Welsh offers a new approach to building up and consolidating learners' fluency and confidence, focusing on the mechanics - the words and phrases that build and drive sentences and make them fit together. 200 Welsh words and phrases are listed alphabetically, explained in clear and accessible language, and given ample exemplification to illustrate their meaning and use. All instances of mutation are marked with the usual typographic signs, and cross-references are given throughout to related entries. Grammatical appendices and an English index round off the manual. Working Welsh is an innovative resource for post-beginner students wishing to explore and master the principal discourse-drivers in modern spoken and standard Welsh"--
Includes index.
OCLC-licensed vendor bibliographic record.
Keywords: Welsh language -- Textbooks for foreign speakers -- English; LANGUAGE ARTS & DISCIPLINES / Journalism